Pengembangan Indikator Bromofenol Biru dan Metil Merah pada Label Pintar sebagai Sensor Kematangan Buah Tomat - Rofiko Nuning Rahayu; Indah Purnamasary; Ari Satia Nugraha (Pustaka Kesehatan, 2022)
The novel on-package color indicator label has been fabricated based on bromophenol blue and a mixture between bromophenol blue and methyl red, and tests have been conducted to assess the ripeness of tomatoes (Lycopersicum commune). Bromophenol blue (BPB) and a mixture between bromophenol blue and methyl red (MM) were immobilized onto the Whatman paper membrane via the adsorption method. The BPB and mixture between BPB and MM/ Whatman paper membrane as color indicator work based on pH decrease as the volatile organic compounds. They are produced gradually in the package headspace during the development of tomato fruit. Subsequently, the combination indicator between bromophenol blue and methyl red changes from purple to red foul conditions, while the bromophenol blue indicator changes from blue to yellow foul conditions that can be seen visually. The results showed the color indicator can be used to determine the maturity conditions of tomatoes (Lycopersicum commune) at room temperature and chiller temperature. Furthermore, there are also changes in several parameters (pH, texture, weight loss, sensory evaluation) that are commonly used for the ripeness characteristics of tomatoes (Lycopersicum commune). Therefore, this indicator can be used for visual monitoring of the maturing of the tomatoes in packaging.